Numerical analysis of heat flow in wall of detonation tube during pulse detonation cycle. (25th March 2021) - Ni, Xiaodong; Weng, Chunsheng; Xu, Han; Bai, Qiaodong
Highlights: The temperature of the wall near high temperature gas isn't always increase. The inner wall temperature have a strong fluctuation during the detonation. The insulating material could reduce the thermal fatigue region of the tube. The temperature gradient of the tube can be alleviated by shortening its length. Increasing the tube diameter is beneficial to heat diffusion. Abstract: The thermal ablation of the detonation tube is a key factor in pulse detonation engine (PDE) research. In this study, a symmetric two-phase detonation model and a cylinder heat conduction model are used for studying the features of transient heat transfer. The effects of the tube material and size on the heat transfer are analyzed using this model. To capture the shock wave simply and accurately, the space–time conservation element and solution element method and the finite-difference method are used for simulating the interior flow and the heat-transfer process of the detonation tube, respectively. The numerical results are consistent with the experimental results. The temperature of the PDE wall increases by 1.5 K per four detonation cycles at a frequency of 20 Hz. Then, the effects of the materials of the tube wall and the diameter and length of the tube are investigated. The inner flow greatly affects the inner-wall temperature, particularly the influence is obvious when the tube materials change. Increasing the diameter can improve the heat dissipation, and reducing the length smooths the temperature gradient along the axis. The results of this study provide guidance for the design of PDEs.